DETERMINANTS SELF SUFFICIENCY OF RICE IN SUPPORTING FOOD INDEPENDENCE - Kurnia, lendi Ageng; Iskandar, Deden Dinar (Universitas Muhammadiyah Ponorogo, 2019)
The research objective is to determine the future trends of rice self-sufficiency and to know the factors that influence rice self-sufficiency so as to achieve food independence. Previous research reviews rice self-sufficiency in terms of production factors. In this study, price stability, rice supply and farmers' welfare are taken into account as research variables. The results showed that the trend of analysis with quadratic models to measure rice self-sufficiency tends to increase. Variables that influence rice self-sufficiency are rice productivity, rice supply stability, application of technology and dummy during the New Order government with reform. Whereas the gap between rice price and grain price, the level of rice consumption and the welfare of farmers, does not affect rice self-sufficiency. The conclusion of this research is that to increase rice self-sufficiency, it is necessary to increase rice productivity, ensure that government rice reserves are always available so as to stabilize food supply stability, and always develop appropriate technological innovations to support increased production.